Examining the Deviation in Energy Saving Estimations Due to the Use of the Degree Days Method - Mokhtar, Ahmed (2022)
Energy performance contracts are commonly used to retrofit buildings and reduce their energy consumption. The financial agreement in the contracts typically depends on calculating the amount of energy saved every year. This is difficult to calculate as many aspects that impact a building’s energy consumption continuously change, including the weather. The Degree Days method is commonly used to help estimate the energy saving while the weather is changing. The Degree Days can be calculated with a variety of base temperatures resulting in different values. This paper is a first step in examining the significance of the deviation in energy saving calculations when using this method. It also investigates if there is a more appropriate base temperature to use for that purpose. Energy simulation with actual annual weather data is used to make the investigation. Two different building types and three different energy conservation measures are used. The results of this preliminary investigation show that the deviation can be significant in some cases. They also show the possibility that a particular base temperature for calculating the degree days can give more accurate savings estimations. These can be very important results for users of energy performance contracts.